Peran Komunikasi Keluarga Dalam Pengambilan Keputusan Pernikahan Dini pada Remaja - Fauziah, Dea Syifa; Tayo, Yanti; Utamidewi, Wahyu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to explain the role of family communication in the decision-making process of early marriage among teenagers. The study utilizes a qualitative descriptive method to gain an in-depth understanding of the observed phenomenon. Data was collected through in-depth interviews with teenagers who have experienced early marriage, their parents, and other family members involved in the decision-making process. The research also involved participatory observation within the teenagers' family environment to obtain a more comprehensive understanding of the social, cultural, and influencing factors of early marriage decision-making. The results of this study indicate that family communication plays a significant role in the decision-making process of early marriage among teenagers. Open, honest, and empathetic communication among family members helps teenagers understand the consequences, risks, and long-term impacts of early marriage. Effective communication also enables families to convey values, norms, and expectations related to marriage to teenagers. Additionally, the research identifies several factors that influence family communication in the context of early marriage decision-making. These factors include social, cultural, economic, educational, and personal factors of the teenagers. Gender inequality, lack of education, cultural pressures, and poverty are some of the factors that influence family communication in the context of early marriage among teenagers. The findings of this research have important implications for the development of programs and interventions aimed at preventing early marriage among teenagers. In the context of family communication, these programs should encourage open communication and support the positive role of the family in helping teenagers make informed decisions and providing realistic understanding of marriage. Keywords: family communication, decision-making, early marriage.